1990
DOI: 10.1083/jcb.111.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Location of B- and Z-DNA in the chromosomes of a primitive eukaryote dinoflagellate.

Abstract: Abstract. The usual conformation of DNA is a righthanded double helix (B-DNA). DNA with stretches of alternating purine-pyrimidine (G-C or A-T) can form a left-handed helix (Z-DNA). The transition B--'Z, facilitated by the presence of divalent cations, cytosine methylation, or constraints on DNA such as superhelicity may play a role in the regulation of gene expression and/or in DNA compaction (Zarling, D. A., D. J. Arndt-Jovin, M. Robert-Nicoud, L. P. Mclntosh, R. Tomae, and T. M. Jovin. 1984. J. Mol. Biol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 61 publications
3
32
0
Order By: Relevance
“…First, it is well known that dinoflagellates have an unusual chromosomal structure and the different size of the PCNA-like protein observed could be related to this variety in dinoflagellate chromosomal structure. It has been shown that dinoflagellates contain extensive stretches of Z-DNA (Soyer-Gobillard et al, 1990) and the C. cohnii PCNA could have a different structure and size to properly interact with the large amounts of Z-DNA (Leveson & Wong, 1999). It is also important to note that dinoflagellates are a transition group from prokaryotic to eukaryotic evolution and they are a very diverse group.…”
Section: Discussionmentioning
confidence: 97%
“…First, it is well known that dinoflagellates have an unusual chromosomal structure and the different size of the PCNA-like protein observed could be related to this variety in dinoflagellate chromosomal structure. It has been shown that dinoflagellates contain extensive stretches of Z-DNA (Soyer-Gobillard et al, 1990) and the C. cohnii PCNA could have a different structure and size to properly interact with the large amounts of Z-DNA (Leveson & Wong, 1999). It is also important to note that dinoflagellates are a transition group from prokaryotic to eukaryotic evolution and they are a very diverse group.…”
Section: Discussionmentioning
confidence: 97%
“…This structure seems to be stabilized by metal cations and structural RNA (Kearns and Sigee, 1980;Dodge, 1985;Soyer-Gobillard and Herzog, 1985). Dinoflagellate DNA has a B configuration with some Z-DNA stretches mostly at the chromosome periphery and in NORs (Soyer-Gobillard et al, 1990). Structural inactive DNA forms the main body of the chromosomes while genetically active DNA localizes in peripheral DNA filaments (Sigee, 1986) where co-transcriptional splicing has also been localized (Alverca et al, 2001).…”
mentioning
confidence: 99%
“…At the ultrastructural level, the nucleofilaments are arranged in a series of parallel nested arches providing a characteristic banding pattern, which has no homology to Q, G or C banding (Haapala and Soyer, 1974a). Transverse bands correspond to the DNA fibrils proceeding across the chromosome and interbands to the fibrils communicating with adjacent bands (Rizzo, 1982;Spector, 1984;Goyanes, 1987, 2005;Soyer-Gobillard et al, 1990). This structure seems to be stabilized by metal cations and structural RNA (Kearns and Sigee, 1980;Dodge, 1985;Soyer-Gobillard and Herzog, 1985).…”
mentioning
confidence: 99%
“…Longitudinal sections of chromosomes show bands of 0.8 Ìm diameter distributed in regular periods of around 100 nm (Costas and Goyanes, 1987). Fiber loops can also be found, protruding at the chromosome periphery (Livolant, 1978;Sigee, 1983Sigee, , 1986Soyer-Gobillard et al, 1990). Since the early studies of dinoflagellate chromosomes, the same question of how the chromatin fibers bend to organize in arches that finally build the dinoflagellate chromosome has arisen.…”
Section: Attempts To Understand the Chromosome Structure In Dinoflagementioning
confidence: 96%